ANALISIS RENCANA ANGGARAN BIAYA PEMBANGUNAN RUMAH TIPE 36 PADA PERUMAHAN DE’CIRCLE SAMARINDA - Mandola, Ramly W Mandola W (EKONOMIA, 2015)
Needs housing company will budget plan is for the company to find out how much it cost to build a house and in addition to the needs of the preparation of financial data is also needed BP consumer installment because most of the development funds based on financial income from the sale of houses, from the above explanation, it can be formulated problem is whether "is housing development Budget Plan type 36 in 2012 Smaller than actual budget cost of housing construction in 2014. This study focused on the activities and progress of financial inclusion field De'Circle Housing built by a limited liability People's House. If seen Budget Plan 36/84 type of housing development that made the company in 2012 amounted to Rp. 86,629,011.64 was not in accordance with the Development Budget Realization in 2014 which has been calculated based on the budget plan in 2012 that the author made on the theory bachtiar ibrahim and have been added to the inflation rise 20% to Rp. 99,545,970.79.